Leveraging resource ecologies for sustainability transitions : a waste management case - Narayan, Rumy; Tidström, Annika (Emerald Publishing Limited, 2020)
Addressing fundamental sustainability challenges has now become strategic for multinational corporations. However, such challenges by their very nature are complex and require resources that are frequently beyond those that are traditionally accepted as relevant and crucial to a firm’s core business operations. The aim of this paper is to illustrate how firms identify and integrate diverse groups of actors using social intelligence to build an ecology of resources to tackle these complex challenges. The empirical part is based on qualitative single case study research of a packaging company and its waste management program. Organizing for sustainability require business activities to be conceptualized as a continuous process of project building, involving actors in diverse settings and responsibilities divided thematically and spatially forming nets within a network to solve problems, collectively. There is a fundamental analytical problem of integrating a diversity of value spheres, and society has a set of rational methods for planning and action where decisions are made to privilege one aspect to the exclusion of others. Artificial separation of activities that are interdependent and failure to allow these activities to evolve through interactions in time and space could threaten sustainability.
Keywords: ecology; networks; resources; social intelligence; sustainability; transition; Strategic management; fi=Johtaminen ja organisaatiot|en=Management and Organization|